Flexibility Culture, Person–Job Fit, and Job Benefits as Predictors of Eudaimonic Workplace WellBeing and Turnover Intention of Employees - Hemavathi, G. P.; T., Frank Sunil Justus (Prabandhan: Indian Journal of Management, 2023)
Purpose: This study aimed to assess the influence of flexible work arrangements, person–job fit, and job benefits on employees’ well-being and turnover intentions. A conceptual framework was proposed to examine how an organization’s flexibility culture and employees’ perceptions of job fit and benefits impacted their eudaimonic well-being and turnover intentions. This study examined the connections between turnover intentions, eudaimonic workplace well-being, employment benefits, and flexibility culture. Through this in-depth investigation, the study offered insightful recommendations to help firms enhance employee well-being, increase retention, and maximize overall organizational success. Methodology: A structured questionnaire was administered to Bangalore, Karnataka’s Information Technology (IT) sector employees. The study garnered 259 valid responses from participants employed in three distinct IT firms. The two-step modeling approach validated the proposed conceptual framework. Structural equation modeling (SEM) was employed for data analysis. Findings: The findings revealed that flexibility culture, person–job fit, and job benefits influenced employees’ eudaimonic well-being, subsequently affecting their turnover intentions. Specifically, flexibility culture and job benefits were found to impact turnover intention and their indirect effects directly. The study highlighted the evolving employee expectations and the importance of fostering well-being within a dynamic work environment. Practical Implications: The study’s practical implications underscored the significance of adopting flexible work arrangements aligning with employees’ job fit and offering favorable benefits. This strategy may help to improve employee satisfaction and reduce plans for turnover. The study’s distinctiveness resided in its comprehensive examination of the relationships among flexibility culture, person–job fit, employment perks, well-being, and turnover intentions in the context of the information technology industry. Originality: The paper’s uniqueness stemmed from carefully analyzing the intricate relationships between several crucial factors and their combined effects on employees’ well-being and intent to leave the company in the evolving organizational landscape.